Thrombocytopenia in COVID-19: Focused Summary of Current Understanding of Mechanisms and Clinical Implications. Issue 7 (13th October 2021) - Singh, Suvir; Sharma, Rintu; Singh, Jagdeep; Jain, Kunal; Paul, Davinder
Abstract : Thrombocytopenia is noted in corona virus disease-2019 (COVID-19) with a prevalence of 5% to 41%, and has been observed to be associated with inferior outcomes. The pathogenesis of thrombocytopenia in COVID-19 is unique and differs from other viral syndromes in terms of clinical presentation and causative mechanisms. Platelets act as both targets and the initial defense against severe acute respiratory syndrome-coronavirus 2 and work in concert with the underlying thrombophilic mechanisms to modulate the final disease phenotype. Understanding these mechanisms may possibly allow targeting of a key component of COVID-19 pathogenesis. We provide a focused review of the current mechanisms implicated in development of thrombocytopenia in COVID-19 and therapeutic implications of the same.